Exploration of migration directions in different populations of Eothenomys miletus in the Hengduan Mountains of Yunnan Province: a genome-based analysis - Cai, Yanfei; Jia, Ting; Zhu, Wanlong (Frontiers in Ecology and Evolution, 2025)
Eothenomys miletus is an endemic species that inhabits the Hengduan Mountain regions (HDR) and serves as one of the primary hosts for plague and hantaviruses. While the physiological characteristics of E. miletus have been extensively studied, the molecular aspects, particularly the migration direction of E. miletus, remain unclear. In the present study, we utilized genomic data to investigate the migration direction of four populations: Ailaoshan (ALS), Jiangchuan (JC), Lijiang (LJ), and Deqin (DQ), which are distributed from south to north within the HDR. Our results indicated that the ALS population is positioned at the base of the phylogenetic tree, and admixture analysis revealed that the ALS population is more closely related to the JC and DQ populations. Integrate the molecular genetic structure, fossil records of E. miletus as well as the results of our research, we inferred that the migration direction of E. miletus may have been from south to north, suggesting that the DQ and JC populations may have originated from the migration of ALS. However, the migration patterns and origins of the LJ population require further investigation and discussion. Additionally, we focused on identifying genomic signatures of selection and local adaptation among the different populations. We identified three selected genes associated with the olfactory placode in DQ: Six1, Six4, and Sox2. We hypothesized that these genes may be linked to the DQ population’s adaptation to the region’s microclimate. In summary, the present study is the first to employ genomics to explore the migration direction of E. miletus, which is crucial for future research on the origins of Eothenomys.